2015
DOI: 10.1002/stem.1866
|View full text |Cite
|
Sign up to set email alerts
|

Mohawk Promotes the Tenogenesis of Mesenchymal Stem Cells Through Activation of the TGFβ Signaling Pathway

Abstract: The transcription factor Mohawk (Mkx) is expressed in developing tendons and is an important regulator of tenogenic differentiation. However, the exact roles of Mkx in tendinopathy and tendon repair remain unclear. Using gene expression Omnibus datasets and immunofluorescence assays, we found that Mkx expression level was dramatically lower in human tendinopathy tissue and it is activated at specific stages of tendon development. In mesenchymal stem cells (MSCs), ectopic Mkx expression strikingly promoted teno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(147 citation statements)
references
References 39 publications
6
139
2
Order By: Relevance
“…In keeping with the findings of the PDL analysis in Mkx −/− mice, gene expression analysis in MKXsilencing and Mkx-overexpression experiments using hPDL fibroblasts revealed that MKX strongly and specifically promotes the expression of a set of extracellular matrix genes related to PDL tissue formation, including COL1A1 and COL1A2, which are similar to those reported in mesenchymal stem cells (Liu et al, 2015;Otabe et al, 2015). In particular, in PDL cells, Postn, which is among the extracellular matrix adhesion molecules mainly expressed in the bone, periosteum, and PDL tissues (KruzynskaFrejtag et al, 2004;Ma et al, 2011;Rios et al, 2005), was significantly decreased in the M1 PDL in 10-week-old Mkx −/− mice in vivo.…”
Section: Discussionsupporting
confidence: 83%
“…In keeping with the findings of the PDL analysis in Mkx −/− mice, gene expression analysis in MKXsilencing and Mkx-overexpression experiments using hPDL fibroblasts revealed that MKX strongly and specifically promotes the expression of a set of extracellular matrix genes related to PDL tissue formation, including COL1A1 and COL1A2, which are similar to those reported in mesenchymal stem cells (Liu et al, 2015;Otabe et al, 2015). In particular, in PDL cells, Postn, which is among the extracellular matrix adhesion molecules mainly expressed in the bone, periosteum, and PDL tissues (KruzynskaFrejtag et al, 2004;Ma et al, 2011;Rios et al, 2005), was significantly decreased in the M1 PDL in 10-week-old Mkx −/− mice in vivo.…”
Section: Discussionsupporting
confidence: 83%
“…Like Scx and Egr1, Mkx can drive bone marrow-derived MSCs towards a tenocyte fate in vitro (Liu et al, 2015;Otabe et al, 2015). However, in mouse embryos the expression of Mkx begins in developing tenocytes later than that of Scx or Egr1/2 (at E13.5-14.5), becoming restricted to tendon sheath cells and collateral ligaments (which stabilize joints) in the limbs by E16.5 (Anderson Smad3 Fig.…”
Section: /Egr2mentioning
confidence: 99%
“…Mkx −/− mutant mice are viable, fertile, and form normal tendons at first with no defects in Scx expression but later exhibit reduced levels of Col1a1, Col1a2, Tnmd, fibromodulin (Fmod) and decorin (Dcn) as well as thinning of collagen fibrils (Ito et al, 2010;Kimura et al, 2011;Liu et al, 2010). Similar to Scx, Mkx can function as a transcriptional activator when complexed with Smad2/3 to promote Col1a1, Col1a2, Tnmd and Dcn expression as well as TGFβ2 expression in murine MSCs (Liu et al, 2015). However, at other promoters it interacts with the Sin3A/ histone deacetylase (HDAC) complex to repress gene expression, including that of key myogenic factors such as MyoD (Myod1), Sox6 and the cartilage determinant Sox9 (Fig.…”
Section: /Egr2mentioning
confidence: 99%
See 2 more Smart Citations